ABA-Dependent and ABA-Independent Functions of RCAR5/PYL11 in Response to Cold Stress - Lim, Chae Woo; Lee, Sung Chul (Frontiers in Plant Science, 2020)
Arabidopsis thaliana has 14 abscisic acid (ABA) receptors—PYR1/PYLs/RCARs—which have diverse and redundant functions in ABA signaling; however, the precise role of these ABA receptors remains to be elucidated. Here, we report the functional characterization of RCAR5/PYL11 in response to cold stress. Expression of RCAR5 gene in dry seeds and leaves was ABA-dependent and ABA-independent, respectively. Under cold stress conditions, seed germination was negatively affected by the level of RCAR5 expression, which was dependent on ABA and was regulated by HAB1, OST1, and ABI5—downstream components of RCAR5 in ABA signaling. Leaves of RCAR5-overexpressing plants showed enhanced stomatal closure—independent of ABA—and high expression levels of cold, dehydration, and/or ABA-responsive genes, compared to those of wild-type; these traits conferred enhanced freezing tolerance. Our data suggest that RCAR5 functions in response to cold stress by delaying seed germination and inducing rapid stomatal closure via ABA-dependent and ABA-independent pathways, respectively.